Human relations in teaching : the dynamics of helping children grow - Lane, Howard ; Beauchamp, Mary; Beauchamp, Mary (New York : Prentice-Hall, 1961)
Human Relations in Teaching is an invitation to be thoughtful. It is written for the friends of younger people. We hope that it will remind parents, teachers, neighbors, and other educators that they began life as children and that life then was as sweet, delightful, challenging, and important as it is to them now. It is written for these friends to study and ponder and thus help them devise ways and schemes for rearing the kind of people who can live happily, productively, and securely in this new world that must learn to control the release of new energies.
Section I. What does it mean to be human -- Section II. What does it mean to live in mid-twentieth century -- Section III. What are the dynamics of learning to live together.
Includes index.
Keywords: EDUCATIONAL PSYCHOLOGY